Faktor-Faktor Yang Memengaruhi Financial Performance Pada Perusahaan Manufaktur (Jurnal Paradigma Akuntansi, 2022)
The purpose of this research is to determine the effect of liquidity, leverage, firm size, audit committee size, and board of commissioners size on financial performance of manufacturing companies listed on Indonesia Stock Exchange in 2017-2019. The samples used in this research are 56 manufacturing companies with a total of 168 data selected using purposive sampling technique. The data in this research are tested using Eviews version 11. The results show that firm size has a negative and significant effect on financial performance, liquidity and leverage have a positive and insignificant effect on financial performance, and audit committee size and board of commissioners size have a negative and insignificant effect on financial performance.